Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.aott.2019.06.001
|View full text |Cite
|
Sign up to set email alerts
|

The safety and the efficacy of computed tomography guided percutaneous radiofrequency ablation of osteoid osteoma

Abstract: Executive Office:Şehremini Mah., Koyuncu Sk., Ciğdem Apt., No: 4, D 5, Fatih, İstanbul, Turkey Phone : +90 212 -530 15 08/21 Fax : +90 212 -530 15 21

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
0
9
0
2
Order By: Relevance
“…CT and MR imaging findings of a total of 152 patients (107 male and 45 female patients; mean age 17.9 years; age range 1-42 years; 66.4 % paediatric; 20% of all were in the first decade of life) with the diagnosis of OO were evaluated retrospectively. The median volume of the lesions was 189 mm 3 (min: 22 mm 3 [7 × 3 × 2 mm]; max: 1287 mm 3 [15 × 15 × 11 mm]). Mean time to hospital admission was 13 months.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CT and MR imaging findings of a total of 152 patients (107 male and 45 female patients; mean age 17.9 years; age range 1-42 years; 66.4 % paediatric; 20% of all were in the first decade of life) with the diagnosis of OO were evaluated retrospectively. The median volume of the lesions was 189 mm 3 (min: 22 mm 3 [7 × 3 × 2 mm]; max: 1287 mm 3 [15 × 15 × 11 mm]). Mean time to hospital admission was 13 months.…”
Section: Resultsmentioning
confidence: 99%
“…Osteoid osteoma (OO) is a benign osteogenic tumour that commonly affects male gender in second decade of life [1][2][3][4]. Diagnosis is based on characteristic clinical and radiological findings.…”
Section: Introductionmentioning
confidence: 99%
“…Eberhardt et al [ 37 ] also reported 3 cases of OO of the acetabulum treated by hip arthroscopy. We found descriptions of several cases using arthroscopic excision and one case using arthroscopy-assisted radiofrequency ablation for the treatment of the OO of the acetabulum [ 1 , 5 , 9 , 10 , 12 , 17 , 20 , 21 , 23 , 37 ]; however, data on patients treated using by hip arthroscopy alone were scare.…”
Section: Discussionmentioning
confidence: 99%
“…OO of the acetabulum is even more rare. In recent literature, we found several case reports on treatment for OO of the acetabulum [ 1 , 5 , 9 23 ]. Minimally invasive percutaneous techniques, including CT-guided approaches and ablation using radiofrequency or lasers, as well as arthroscopic excision techniques for OO in acetabulum, have been described.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, six patients suffered operative complications (7.9%), including three cases of skin numbness, one case of puncture site infection, one case of radial nerve injury and two-stage skin burn, and one case of three-stage skin burn 13,14,[23][24][25][26] . More patients with osteoid osteoma in extremities have been treated by percutaneous radiofrequency ablation 27,28 . The new view is that microwave ablation of osteoid osteoma provides fast heating and short ablation time, avoids skin burns caused by electrode pieces, and is not affected by pacemakers, among other factors.…”
Section: Recommendation 1: Percutaneous Microwave Ablation Of Osteoidmentioning
confidence: 99%